Frailty in orthopaedics: is age relevant?. Issue 11 (November 2020) - Rogers, Michaela; Brown, Robyn; Stanger, Sophie
Highlights: There is increasing recognition of frail patients in all age groups sustaining fragility fractures. Frailty is being increasingly recognised as a global indicator of patient outcomes irrespective of age. Clinical Frailty Scale should take precedence over age when ascertaining clinical priority. Abstract: Over the last decade, national guidelines and the Best Practice Tariff (BPT) have been created to incentivise quality care in patients aged over 60 with hip fractures. This has resulted in significantly decreased length of stay, mortality and post-operative complications in this patient cohort. However, there is increasing recognition of frail patients in all age groups sustaining all fragility fractures. Until recently, these patients experienced poorer outcomes and were excluded from the dedicated care pathways that hip fracture patients received. The BPT and other national guidelines are now expanding inclusion criteria into care packages between guidelines which were initially reserved for hip fracture patients. This expansion is placing increasing pressure on limited NHS resources. Current variations between society guidelines risks producing regional and departmental inconsistencies in care. There is therefore a need to provide consistent guideline targeted at the most vulnerable trauma patients of this expanded cohort. Although the current BPT applies to over 60s only, there is limited evidence to support age-related prognosis in trauma. In contrast, frailty is being increasingly recognised as a global indicator of patient outcomes irrespective of age, with use of Clinical Frailty Scale (CFS) being adopted in various medical fields. BOAST is already using CFS as an inclusion criterion for major trauma and there is increasing data to suggest that frail trauma patients benefit most from comprehensive geriatric care and expedient time-to-operation. We suggest that CFS should take precedence over age when ascertaining clinical priority and producing Best Practice Tariffs. Further research is required to investigate frailty-related outcomes in trauma and the impact of comprehensive care bundles on the outcomes of frail orthopaedic patients.